Clinico–pathological study of hysterectomy in benign lesions: a study of 379 hysterectomies - Fatehpuriya, Dharmendra Singh; Verma, Leena; Sharma, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterus is a very vital reproductive organ and is subjected to many benign and malignant diseases. Hysterectomy is one of the most frequently performed procedures all over the world. Aims and Objectives of the work was to study the clinical benign indications of hysterectomy specimens and to correlate the findings with the histopathological reports. Methods: A prospective and randomized study was performed in 379 cases of elective hysterectomies for benign lesions. Results: Abdominal hysterectomy was performed in 64.6% cases while vaginal hysterectomy accounted for 35.3% cases. The mean age for hysterectomy was 45 years with a range from 14 to 78 years. Patients mostly presented with menstrual irregularities (34.3%) followed by prolapse uterus (30%). The principle indication of elective hysterectomy was leiomyoma and was present in 197(51.9%) patients, followed by prolapse uterus in 134 (35.3%) and dysfunctional uterine bleeding (DUB) in 26 (6.8%) patients. Maximum numbers of cases of leiomyoma, uterine prolapse and DUB were found in age group of 41-50 yrs. Conclusions: The number of abdominal hysterectomy was more than vaginal hysterectomy. Most common presenting feature was menstrual related symptom followed by prolapsed. The main indication for elective hysterectomy was leiomyoma, prolapsed and DUB.